A Stage for the Outsiders of Neoliberal Capitalism: Dublin’s Gate Theatre, European Austerity and #WakingTheFeminists - Francesco Sani (Review of Irish Studies in Europe, 2021)
This essay analyses Selina Cartmell’s first season as artistic director of Dublin’s Gate theatre, in 2018 in relation to the development of neoliberalism in Ireland and the part played by the European Union in this process. Key social and political contexts are identified in order to frame this analysis, including the concentration of power in the upper-classes distinctive of neoliberalism; the relevance of historical memory in Irish culture; the restructuring of the Irish Arts Council in consequence of post-2008 austerity; and, the influence of #WakingTheFeminists’ protests against the marginalisation of women in the Irish theatre. It is argued that Selina Cartmell successfully fostered the reception of a grassroots movement (#WakingTheFeminists) into a mainstream institution (the Gate, Dublin). However, attention is brought to a pattern of homologation to neoliberal hegemony within such reception, determined by the influences of national (Irish) and supranational (EU) interventions. The article concludes with a reflection on the possibility of counter-performances resistant to neoliberal hegemony within the current Irish and European cultural industry and in the new contexts of the Covid 19 pandemic.